Upaya Peningkatan Engagement Media Sosial Instagram Oleh Media Parapuan - Nizarisda, Tsany Lathifa; Zubair, Feliza; Ramdan, Ahmad Taufiq Maulana (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
Social media is very effective for disseminating information because of its wide scope. This encourages Parapuan to use social media to build brand awareness as a new online media for women. The purpose of this study is to describe the management of Instagram @cerita_parapuan by Parapuan. This study uses the concept of The Circular Model of SOME which is a communication process in developing social media management tactics. This model consists of four stages; share, optimize, manage, engage. This research uses descriptive research method. Data collection techniques through interviews, observation, and literature study. Data validation through data source triangulation techniques. The results of this study are (1)The Share stage, Parapuan use Instagram because it is most effective and suitable for the target audience, in building public trust they try to form an environment like friends; (2) The Optimize stage, Parapuan searches for trending information manually on various platforms. Parapuan engages in conversation by turning trending news into content; (3)The Manage stage, media monitoring is carried out manually and using Keyhole tools, but efforts to respond quickly and interact in real-time are still not optimal; (4) The Engage stage, Parapuan engaging professionals and only involve them in Instagram Live. This effort hasn’t been maximized because audience interaction hasn’t been fulfilled and the factors refers to the influencers involved. The target audience has been determined by the management, and efforts to reach the audience by holding giveaways and uploading content on prime time hours.